Islamic Finance and Energy Efficiency Investments: Mapping Trends via Bibliometrics - Airout, Rula (International Journal of Energy Economics and Policy, 2025)
This study examines the intersection of Islamic finance and energy efficiency investment within a bibliometric analysis, tracing trends and research tendencies from 1979 through early 2025. Utilizing a set of 125 articles, citation, co-authorship, and co-citation analyses were utilized in evaluating productive authors, journals, and topical trends. Results show greater emphasis on green sukuk, renewable energy, sukuk, and sustainability, with certain products like green sukuk being in the limelight in financing green projects. A-list journals like Energy Policy and Energy Economics dominate the productivity, reflecting Elsevier’s dominance in developing this field of research. The fact that there is joint research comprising researchers from China, Malaysia, the USA, and Iran confirms the global outlook of the research. Practical implications are to include openness of trade, environmental pollution, and international investment in Islamic finance mechanism research with the aim of solving energy issues. The paper provides researchers with an overview of potential disciplines, methodologies, and collaborators and highlights the need for cross-disciplinary approaches. The discussion provides a foundation for synthesizing Islamic finance principles and global sustainability goals and charts an agenda for future research and policy development.